The Effect of the PORPE Strategy on Reading Comprehension Attainment - Risnawati - -; Welly - Ardiansyah (Politeknik Negeri Sriwijaya, 2013)
The purposes of the research were to investigate the effect of the PORPE strategy on students' reading comprehension attainment scores, differences of the scores between the male and female students, and significance of group and gender effects on the students' scores. The non equivalent pre-test and post-test design was applied. the research subject were 80 second semester students in the 2012/2013 academic year at English Department of Sriwijaya State Polytechnic. To collect the data, 40 multiple choice questions of reading comprehension test were used. The data were analyzed with t-test and multiple regression test. The research findings showed that: (1) the application of the PORPE strategy could significantly improve students' reading comprehension attainment scores in the experimental group compared with the control group (54.63-71.13 against 52.88 -60.13); (2) the male students' reading comprehension attainment scores were higher than the female students' scores; and (3) the sex and group had a significant effect on the attainment scores of the studentsKeywords: Reading comprehension, PORPE, t-test, multiple regression, outlier